Mexico : Review Under the Flexible Credit Line Arrangement-Press Release and Staff Report. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2020)
The Covid-19 shock this year has imposed an enormous strain on Mexico. Beside the staggering human cost, the economy faces a historic drop in output and employment and a sharp spike in poverty. It is expected to take many years for employment, income, and poverty to return to pre-pandemic levels.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet